Two Dimensional Indecomposable Modules over Infinite Dimensional Hereditary Path Algebras (Communications in Mathematical Research, 2021)
Non-isomorphic two dimensional indecomposable modules over infinitedimensional hereditary path algebras are described. We infer that none of them canbe determined by their dimension vectors.
Keywords: infinite dimensional hereditary path algebra; path algebra; quiver representation; indecomposable module.